The use of complex radionuclide methods in the detection of metastatic lesions of the skeleton and liver in kidney cancer - Lazar, Yehor; Yevdoshenko, Danylo; Mazur, Anastasiya; Mіronova , Olena; Romanenko, Нanna; Makarenko, Anatoly (The Ukrainian Scientific Medical Youth Journal, 2025)
metastasis of kidney cancer occurs to the bones in 30% of cases, and to the liver in 60%. One of the radiation methods for detecting metastatic lesions of the skeleton and liver is radionuclide. Osteoscintigraphy is a specific study in the diagnosis of bone metastases, mainly of the osteoblastic type. For the diagnosis of liver metastases, radionuclide methods are used "in vivo" and "in vitro". Static hepatoscintigraphy, compared to ultrasound, computed tomography and magnetic resonance imaging, is less informative in finding secondary lesions. One of the most sensitive methods for detecting secondary liver damage is radioimmunoassay of specific tumor markers. The main ones are alpha-fetoprotein, carcinoembryonic antigen and carbohydrate antigen 19-9. Their concentration in the blood serum increases tenfold when the malignant process spreads to the liver. In the radionuclide department of the KMCL No. 18, which is located at the Department of Radiology and Radiation Medicine of the O.O. Bogomolets National Medical University, patient S., 62 years old, with right-sided renal cell carcinoma of stage II (T2N0M0), underwent radionuclide studies of the skeleton, liver, function of the single left kidney (after right-sided nephrectomy), and tumor markers. The reason for this was the absence of secondary lesions of these organs on X-ray computed tomograms in the presence of pain syndrome in the lower back and heaviness in the right hypochondrium. Radionuclide examination of the skeleton revealed slight hyperfixation of the radiopharmaceutical (up to 150%) from L1 to L5, which did not confirm the presence of secondary spinal lesions. The functional capacity of the left kidney was reduced. The absence of drug accumulation on hepatoscintigram was not detected, but a diffuse-uneven decrease in its uptake by cells of the reticuloendothelial system was observed, which is characteristic of hepatitis. However, the levels of tumor markers characteristic of focal liver damage significantly exceeded the norm. Based on which a conclusion was made regarding metastatic damage to this organ. Thus, patients with hepatocellular kidney cancer are recommended to undergo a comprehensive radiation examination with the inclusion of radionuclide methods both "in vivo" and "in vitro" to determine tumor markers specific for secondary liver damage.